Americana bei Jean Bodin und Johann Fischart, Hexen bei Jean de Léry: zur Funktionalisierung indigener Völker im dämonologischen Diskurs - Perplies, Helge (Scientia poetica, 2022)
The scope of Early Modern Demonology is universal, for the perceived threat of the devil is omnipresent, stretching through time and space. This article examines various utilizations of the description of central and south American indigenous peoples in demonological discourse. By means of three closely related examples, I will demonstrate the discursive conflation of deviant behavior in Europe and in America through comparisons and transferences: Jean Bodin’s Démonomanie des Sorciers (1580), its German translation by Johann Fischart (1581/1586), and Jean de Léry’s writings, especially his Histoire d’un voyage (1578/1585). Within this discursive nexus, Léry compares the American Indigenes to European Catholics, whereas Bodin compares them to European witches - and Fischart completes this argumentative triangle by calling for European Catholics to be held accountable for comparable acts in the same way as European witches.